Hes1 expression in mature neurons in the adult mouse brain is required for normal behaviors - Matsuzaki, Tadanobu (Sci Rep, 2019)
Hes1 regulates the maintenance and proliferation of neural stem/progenitor cells as an essential effector of the Notch signaling pathway. Although Notch signaling is also involved in the functions of mature neurons in learning and memory and in the risk factors for mental disorders such as schizophrenia and bipolar disorder, the in-vivo role of Hes1 in mature neurons remains unknown. Here, we found that Hes1 is expressed by subsets of both excitatory and inhibitory neurons in the adult mouse brain, and that Hes1 expression is induced by neuronal stimulation. Furthermore, inactivation of Hes1 in excitatory neurons resulted in abnormal fear and anxiety behaviors concomitantly with higher neuronal excitability in the amygdala, while inactivation of Hes1 in inhibitory neurons resulted in increased sociability and perseverative tendencies. These results indicated that Hes1 is functionally important for normal behaviors not only in excitatory neurons but also in inhibitory neurons in the adult brain.